“EFFECTIVE TEACHING METHODS FOR DESCRIPTIVE GEOMETRY AND ENGINEERING GRAPHICS IN HIGHER EDUCATION USING DIGITAL TECHNOLOGIES” - Shodiev Furqat Davranovich (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article examines effective teaching methods for the course “Descriptive Geometry and Engineering Graphics” in higher education, focusing on the integration of digital technologies and modern pedagogical approaches. The study highlights how computer-aided design (CAD) software, simulations, and interactivetools enhance students’ spatial reasoning, precision, and problem-solving skills. It also discusses the benefits of combining traditional teaching methods with technological innovations to improve student engagement and prepare learners for professional engineering tasks.